Pemodelan Dua Dimensi Hidrodinamika Untuk Mengestimasi Potensi Energi Arus Laut Di Selat Sunda, Selat Bali Dan Selat Sape - Juventus Welly; Fitri Riandini; Teti Kurniati (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2012)
Research to estimate the potential energy generated by ocean currents was done by using two-dimensional hydrodynamic models. The breadth of the waters of Indonesia provides the advantage to tap the potential energy generated by tides, waves and ocean currents. In narrowed straits, bays or other places ocean currents can be very strong and potential for energy utilization. Studies were conducted on the potential of ocean currents in the Sunda, Bali and Sape (East Nusa Tenggara) Straits. Flow velocity potential is used to calculate the percentage of incident flow velocity greater than 1 m/ s. The simulation results indicated that maximum flow velocity occurred at full moon with a condition from ebb to tide and low tide to tide. locations showing a large enough percentage are the Sunda Strait east of Panjurit Island, Bali Strait west of Tanjung Batulicin, and Sape Strait between the islands Matagateh and Sapekah. For each location, the percentage of maximum current events during one year ranged from 40% to 70%.